Analysis Of Accounting Information Systems Utilization At Pt Raudah Berkah Mulia To Improve Financial Efficiency And Accuracy - Egia Mintania Sri Rezeki Sembiring; Renny Maisyarah; Dwi Saraswati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the use of an Accounting Information System (AIS) at PT Raudah Berkah Mulia to improve financial efficiency and accuracy. The research method used was a qualitative approach through interviews, observation, and documentation. The results indicate that AIS implementation can accelerate the recording process, reduce manual recording, and improve the accuracy and consistency of financial data. Although there are still technical obstacles and limited user understanding, the AIS has an overall positive impact on the company's financial efficiency and accuracy